A smart IoT-based hydroponics system for small-scale household in Bangladesh - Md. Abdul Awal; Aditi Saha Pio; Mushfaka Jannat Mim; Pronab Kumar Paul Partha; Md. Abdullah Al Kafi; Shareen Farha (Smart Agricultural Technology, 2025)
In Bangladesh, intensified growth in populations, diminishing arable area, and traditional farming strategies have stunted soil fertility and crop yield. Hydroponic systems become more preferred as a viable alternative for beneficial production of agriculture. Precise environmental monitoring is essential for maximizing yields; yet, existing data collection techniques are laborious and time-consuming. Real-time monitoring of essential factors in hydroponic systems may successfully mitigate these substantial obstacles to improving crop performance. This study developed an IoT-based automated monitoring and control system for the continuous measurement of important hydroponic parameters, including pH, temperature, total dissolved solids (TDS), and electrical conductivity (EC) and conducted it with the spinach (Spinacia oleracea) plant for field tests. The system incorporated sensors with a microcontroller and relied on Wi-Fi connection for real-time data processing through a developed mobile application. Performance testing showed good precision, with percentages of errors of 0.001 % (pH), 0.306 % (temperature), 0.062 % (TDS), and 0.002 % (EC) compared to the observed and measured data. The system automatically activated relays to regulate acid and nutrient control pumps when parameters fell below thresholds, notifying users through the mobile app for prompt intervention. After implementing this system for spinach cultivation, ideal conditions were maintained consistently, resulting in an average value of pH 6.08 ± 0.15, temperature 26 ± 1.2 °C, TDS 1150 ± 198 ppm, and EC 1.7 ± 0.45 mS/cm, approximately. Hence, this developed technology offered a feasible solution for hydroponics management issues and could be adopted extensively to improve agricultural productivity.